EFFECTIVENESS OF LOCAL-R LEARNING MODEL ON STUDENTS' LEARNING MOTIVATION IN SCHOOLS - Handayani, Fatimah Citra; Bambang, Bambang; Yusman, Beny (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Study This aims To ensure the effectiveness of learning models based on Literacy – Orientation – Collaboration – Reflection (LOK-R)towards motivation Study students at school. Research conducted with Library Research methods or Literature reveals the connection between learning models and motivation Study students. This is done because of learning models and motivation. The study has two keys. The main one correlates with the learning process in class. In addition, that study also discusses the implementation of the LOK-R learning model. From the results, the study concluded that the LOK-R learning model has proven very effective because it can increase the motivation of the Study as well as the enthusiasm of participants in the learning process.